SOME BASIC CONCEPTS OF ACCOUNTING AND THEIR IMPLICATIONS. - Lorig, Arthur N. (The Accounting Review, 1964)
Abstract The article informs that there are certain basic over-all concepts regarding the fundamental nature of business and other organizations from which one reasons to arrive at some accounting decisions, including aspects of classification, measurement and reporting. These concepts are variously termed theories, schools of thought, view- points, conventions, approaches, methods of viewing, and even doctrines. They are so different from one another that they lead to different conclusions or accounting decisions. This often results in controversy and sometimes confusion and misunderstanding. Two of the concepts are widely held-the proprietary and the entity concepts. Other concepts or theories have been proposed as being improvements upon or more realistic than the two mentioned. These include the fund theory, the enterprise theory and the residual equity theory. This paper is divided into two parts. Definitions and a somewhat general discussion of the concepts were found to be necessary and are taken up in Part I. The areas of conflict arising out of the existence of the differing concepts are disclosed in Part II. Readers who tend to be impatient with theoretical discussions may wish to turn to Part II first to see if the disclosures are of interest to them.